Kritik Terhadap Konsep Dasar Zakatnomics (Indeks Pembangunan Zakatnomics) - Adrianna Syariefur Rakhmat; Busaid Busaid (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Zakatnomics is a combination of zakat and economics. In other word, it can be termed as the economics of zakat which examines the concept of economic aspects of zakat in the macro and micro scope. This concept is based on 4 pillars of zakatnomics development, namely (1) faith, (2) productivity, (3) economic justice including the potential for halal industry and (4) Zakat Infaq, Shadaqah and Waqf institutions or ZISWAF. This study is a critical analysis of the Index compiled by the Center for Strategic Studies of BAZNAS, the Zakatnomics Development Index. Based on the 4 pillars of zakatnomics development, only the fourth pillar regarding zakat institutions has not been criticized. While the other 3 pillars have been criticized, although there is a regulatory dimension in the first pillar and a dimension of the government's role in the second pillar that have not been criticized.